PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI, PEMANFAATAN TEKNOLOGI INFORMASI DAN LITERASI KEUANGAN TERHADAP KINERJA USAHA MIKRO (UM) DI KABUPATEN NGANJUK - Diva, Beiby Sukma; Linawati; Kurniawan, Andy (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the effect of accounting system implementation, information technology utilization, and financial literacy on the performance of kinerja usaha mikro (UM) in Nganjuk Regency. Micro-enterprise performance is a crucial aspect in assessing the success and desirability of a business, influenced by various internal factors, including financial management, technology utilization, and financial literacy. This study employed a quantitative approach with a causal comparative approach. A sample of 100 micro-enterprises was selected using a purposive sampling methode technique with specific criteria. Data were collected through a closed-ended questionnaire with a Likert Scale, and data analysis was performed using multiple linear regression with the assistance of SPSS version 30 software. The results indicate that, partially, accounting information system implementation, information technology utilization, and financial literacy have a positive and significant effect on micro-enterprise performance. Simultaneously, these three variables also significantly influence micro-enterprise performance in Nganjuk Regency. The adjusted R-square value of 0.476 indicates that 47.6% of the variation in micro-enterprise performance can be explained by the model developed in this study. These findings confirm that improving financial recording systems, implementing information technology, and strengthening financial literacy are crucial factors in supporting the growth and competitiveness of micro-enterprises. This research provides practical implications for micro-enterprises to optimize technology-based financial recording and increase financial capacity through financial literacy. Furthermore, the results are expected to serve as a reference for local governments and business support institutions in designing digital and financial-based MSME empowerment strategies.